Low levels of awareness despite high prevalence of schistosomiasis among communities in Nyalenda informal settlement, Kisumu city, western Kenya. - Gladys O Odhiambo; Rosemary M Musuva; Vincent O Atuncha; Elizabeth T Mutete; Maurice R Odiere; Rosebella O Onyango; Jane A Alaii; Pauline N M Mwinzi (PLoS Neglected Tropical Diseases)
Introduction Intestinal schistosomiasis is widely distributed around Lake Victoria in Kenya where about 16 million people in 56 districts are at risk of the infection with over 9.1 million infected. Its existence in rural settings has been extensively studied compared to urban settings where there is limited information about the disease coupled with low level of awareness. This study therefore assessed community awareness on existence, signs and symptoms, causes, transmission, control and risk factors for contracting schistosomiasis as well as attitudes, health seeking behaviour and environmental antecedents that affect its control so as to identify knowledge gaps that need to be addressed in order to strengthen schistosomiasis control interventions in informal urban settings. Methods The study was carried out in an informal urban settlement where the prevalence of intestinal schistosomiasis was previously reported to be the highest (36%) among the eight informal settlements of Kisumu city. The study adopted cross-sectional design and purposive sampling technique. Eight focus group discussions were conducted with adult community members and eight key informant interviews with opinion leaders. Data was audio recorded transcribed, coded and thematically analyzed using ATLAS.ti version 6 software. Results Most respondents stated having heard about schistosomiasis but very few had the correct knowledge of signs and symptoms, causes, transmission and control of schistosomiasis. However, there was moderate knowledge of risk factors and at high risk groups. Their attitudes towards schistosomiasis and its control were generally indifferent with a general belief that they had no control over their environmental circumstances to reduce transmission. Discussion/conclusion Although schistosomiasis was prevalent in the study area, majority of the people in the community had low awareness. This study, therefore, stresses the need for health education to raise community's awareness on schistosomiasis in such settings in order to augment prevention, control and elimination efforts.